Pathogenicity assessment of Shiga toxin-producing Escherichia coli strains isolated from wild birds in a major agricultural region in California - Carter, Michelle Qiu; Quiñones, Beatriz; Laniohan, Nicole; Carychao, Diana; Pham, Antares; He, Xiaohua; Cooley, Michael (Frontiers in Microbiology, 2023)
Shiga toxin-producing Escherichia coli (STEC) consists of diverse strains differing in genetic make-up and virulence potential. To better understand the pathogenicity potential of STEC carried by the wildlife, three STEC and one E. coli strains isolated from wild birds near a major agricultural region in California were selected for comparative pathogenomic analyses. Three American crow (Corvus brachyrhynchos) strains, RM9088, RM9513, and RM10410, belonging to phylogroup A with serotypes O109:H48, O9:H30, and O113:H4, respectively, and a red-winged blackbird (Agelaius phoeniceus) strain RM14516 in phylogroup D with serotype O17:H18, were examined. Shiga toxin genes were identified in RM9088 (stx1a), RM10410 (stx1a + stx2d), and RM14516 (stx2a). Unlike STEC O157:H7 strain EDL933, none of the avian STEC strains harbored the pathogenicity islands OI-122, OI-57, and the locus of enterocyte effacement, therefore the type III secretion system biogenesis genes and related effector genes were absent in the three avian STEC genomes. Interestingly, all avian STEC strains exhibited greater (RM9088 and RM14516) or comparable (RM10410) cytotoxicity levels compared with EDL933. Comparative pathogenomic analyses revealed that RM9088 harbored numerous genes encoding toxins, toxins delivery systems, and adherence factors, including heat-labile enterotoxin, serine protease autotransporter toxin Pic, type VI secretion systems, protein adhesin Paa, fimbrial adhesin K88, and colonization factor antigen I. RM9088 also harbored a 36-Kb high pathogenicity island, which is related to iron acquisition and pathogenicity in Yersinia spp. Strain RM14516 carried an acid fitness island like the one in EDL933, containing a nine gene cluster involved in iron acquisition. Genes encoding extracellular serine protease EspP, subtilase cytotoxin, F1C fimbriae, and inverse autotransporter adhesin IatC were only detected in RM14516, and genes encoding serine protease autotransporter EspI and P fimbriae were only identified in RM10410. Although all curli genes were present in avian STEC strains, production of curli fimbriae was only detected for RM9088 and RM14516. Consistently, strong, moderate, and little biofilms were observed for RM9088, RM14516, and RM10410, respectively. Our study revealed novel combinations of virulence factors in two avian strains, which exhibited high level of cytotoxicity and strong biofilm formation. Comparative pathogenomics is powerful in assessing pathogenicity and health risk of STEC strains.